Destsign: sistema web para em escrita em signwriting - Medeiros, Alex Alves de (2023)
The Portuguese language, in the written modality, is a second language for the deaf subject who signs Brazilian Sign Language (Libras). These two languages are structured in different ways: Portuguese is an oral-auditory language and sign language is a visual-spatial language. Libras is the way deaf people express themselves and communicate naturally in the country, and because they are inserted in a society based on the hearing language, it means that obtaining knowledge through reading and writing is something difficult to access since there are few ways available for such purposes in their mother language, in addition, the deaf have gaps in the command of Portuguese precisely because this language is based on being a listener. Thus, the present work, through a qualitative-interpretative approach and using the Design Science Research (DSR) method, aimed to develop a web system to provide the writing of signs in SignWriting, which is a widely disseminated format in Brazil. and in the world, to provide deaf people with an environment in which they can write in a writing system anchored in their mother language. The solution presents as a differential the writing of signs in sequence and how to organize them. For evaluation, the instruments used were practical activities and a questionnaire applied at CAS Natal and online with participants from other states. In this way, usability tests and evaluation of the software were carried out with 8 participants, 6 deaf and 2 hearing, whose analysis of the results proved to be satisfactory as the usability, in general, was well evaluated and that the participants considered that the software contributes to the strengthening of SignWriting and the creation of materials in this writing system.